PRACTICAL PRINCIPLES OF ORGANIZING THE EDUCATIONAL PROCESS (Web of Teachers: Inderscience Research, 2024)
This article talks about the reforms implemented in the education system in recent years, the organizational and pedagogical conditions of the educational process, problems in the organization of the educational process and their solutions, tasks to be performed, etc.